Financial technology and financial inclusion in Zambia - Mwela, Mwaba (Graduate School of Business (GSB), 2025)
Financial inclusion as defined by the World Bank means that individuals and businesses have access to useful and affordable financial products and services that meet their needs through transactions, payments, savings, credit and insurance delivered in a responsible and sustainable way. It is a widespread topic globally, with the potential to severely reduce poverty and the gender gap in developing countries. One area that can drive the financial inclusion agenda is digitization. This study sought to examine the impact of financial technology on financial inclusion in Zambia. With FinTech's global influence evident, the research aimed to ascertain its specific implications for Zambian financial inclusion, considering the country's unique challenges and opportunities related to the integration of technology. Three core questions guided the research: (i) the correlation between financial technology and financial inclusion, (ii) the influence of financial literacy campaigns on financial inclusion in Zambia, and (iii) the influence of socio-demographic factors on financial inclusion in Zambia. The study used a quantitative method to look into the connection between different factors that affect financial inclusion, such as socio-demographic variables and drivers like financial technology, financial literacy, and financial advice. The drivers were based on a 2020 FinScope survey data set with information from over 12 000 people. The results of the data analysis suggest no significant relationship between the usage of financial technology and financial inclusion (both formal and informal), indicating that FinTech did not have an impact on financial inclusion. The low levels of digital financial usage, with only 0.8% of the respondents utilizing financial technology, underscore the notion that access does not necessarily lead to increased usage. Financial literacy, a perceived critical factor, had a significant relationship with financial inclusion in the Zambian context. In spite of financial literacy being a critical driver, the region had the highest correlation and was considered the key driver for the respondents in the sample. This indicates the critical role that infrastructure plays in driving financial inclusion in a country like Zambia. Leveraging other research, the challenges identified are mostly associated with usage and hence may lean on financial literacy awareness. Increased access does not necessarily translate to more usage. The Zambian government can focus on the drive towards increasing usage of digital platforms by addressing the infrastructure that inhibits usage. We should prioritize addressing the barriers to accessibility and usage of digital financial services, given the region's significant impact on financial inclusion. In addition, institutions vii should enhance digital platforms to support the drive towards online payments and digitization in underserved areas. This will require a level of financial literacy if it is to yield the desired results. Formal institutions should collaborate with informal groups to provide more formalized banking options, ensuring the essence of communal trust remains intact. Further, institutions should understand the challenges faced by different age groups and adapt services to cater to varying age demographics, taking cultural influences into consideration. These recommendations provide a framework for financial institutions in Zambia to bolster financial inclusivity and align their services more closely with the populace's needs.